Digital Epidemiology in the Post-pandemic Era: Opportunities and Gaps in Public Health Surveillance - Sajid, Ammaz; Anam, Maria; Salahudin, Amna; Safdar, Umair; Sajid, Aitzaz; Riaz, Alina (International Health Review, 2025)
The COVID-19 pandemic has irreversibly changed our approach to public health surveillance, piloting the widespread use of digital epidemiological tools and exposing new possibilities along with ongoing deficits in our surveillance architecture. The current study looked at recent developments in digital epidemiology during the post-pandemic period in terms of evolution, opportunities, and challenges. The study presented important opportunities, such as the ability to provide real-time surveillance, democratized access to epidemiological data, and integrated data sources. Furthermore, it also identified common challenges surrounding data privacy rules, digital divide, technical constraints, and governance systems. It demonstrated that although digital epidemiology holds great promise to improve public health surveillance, to fulfil it, the community must grapple with such key challenges as interoperability, equity, trust, and governance. These findings underscore the need for the post-pandemic period (2020–2025) to be a policy window of opportunities where it would be possible to build strong digital surveillance systems that are sustainable, equitable, and can effectively meet the needs of future public health emergencies whilst protecting individual rights and promoting health equity.